Increased complement factor B and Bb levels are associated with mortality in patients with severe aortic stenosis - Shahini, Negar; Ueland, Thor; Auensen, Andreas; Michelsen, Annika E.; Ludviksen, Judith K.; Hussain, Amjad I.; Pettersen, Kjell I.; Aakhus, Svend; Espeland, Torvald; Lunde, Ida G.; Kirschfink, Michael; Nilsson, Per H.; et al. (The journal of immunology, 2019)
Inflammation is involved in initiation and progression of aortic stenosis (AS). However, the role of the complement system, a crucial component of innate immunity in AS, is unclear. We hypothesized that circulating levels of complement factor B (FB), an important component of the alternative pathway, are upregulated and could predict outcome in patients with severe symptomatic AS. Therefore, plasma levels of FB, Bb, and terminal complement complex were analyzed in three cohorts of patients with severe symptomatic AS and mild-to-moderate or severe asymptomatic AS (population 1, n = 123; population 2, n = 436; population 3, n = 61) and in healthy controls by enzyme immunoassays. Compared with controls, symptomatic AS patients had significantly elevated levels of FB (2.9- and 2.8-fold increase in population 1 and 2, respectively). FB levels in symptomatic and asymptomatic AS patients were comparable (population 2 and 3), and in asymptomatic patients FB correlated inversely with valve area. FB levels in population 1 and 2 correlated with terminal complement complex levels and measures of systemic inflammation (i.e., CRP), cardiac function (i.e., NT-proBNP), and cardiac necrosis (i.e., Troponin T). High FB levels were significantly associated with mortality also after adjusting for clinical and biochemical covariates (hazard ratio 1.37; p = 0.028, population 2). Plasma levels of the Bb fragment showed a similar pattern in relation to mortality. We concluded that elevated levels of FB and Bb are associated with adverse outcome in patients with symptomatic AS. Increased levels of FB in asymptomatic patients suggest the involvement of FB from the early phase of the disease.